Pelatihan Software Design Bagi Pendidik di Lingkungan TKIT Mekar Insani Untuk Meningkatkan Pembelajaran Interaktif - Arita Witanti; Triana Noor Edwina D.S; Supatman (CV. Multi Kreasi Media, 2023)
The education post-pandemic needs more preparation for the teachers. One of the preparation tools is instructional media. Using instructional media increases students' concentration during the transformation of educational material. This fact is the opposite of education without instructional media. On the other hand, less interaction between the teacher and student after the post-pandemic force the teacher to know about building bonding during the learning process. From the previous interview with stakeholders, a solution to solve the problem was making training of canva to upgrade the knowledge of making interactive learning media. There was some materials have been transformed. There were canva installation, login, account use, feature introduction, practice session, and Q and A. For the production one design, we should ATM rules. That was observed imitation modifications. This activity concluded that teachers could make some designs using canva.